2020
DOI: 10.1002/ijc.33422
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of chronomodulated irinotecan, oxaliplatin, 5‐fluorouracil and leucovorin combination as first‐ or second‐line treatment against metastatic colorectal cancer: Results from the International EORTC 05011 Trial

Abstract: The triplet combination of irinotecan, oxaliplatin and fluorouracil is an active frontline regimen in metastatic colorectal cancer, but scarce data exist on its use as salvage treatment. We aimed at assessing its safety and efficacy profiles with its circadian‐based administration (chronoIFLO5) as either first‐ or second‐line treatment, within the time‐finding EORTC 05011 trial. Five‐day chronoIFLO5 was administered every 3 weeks in patients with PS 0, 1 or 2. It consisted of chronomodulated irinotecan (180 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Thus, timing drug administration may also impact drug pharmacodynamics (PD) and eventually treatment outcome. In the field of cancer management, several clinical studies have addressed the effect of timing medications for treatment optimization – chronotherapy – with promising results [8] , [12] , [13] , [14] . Giacchetti and colleagues reported data from three international Phase III clinical trials involving 842 patients (345 females and 497 males) treated with 5-fluorouracil, leucovorin and oxaliplatin administered as chronomodulated or conventional infusions [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, timing drug administration may also impact drug pharmacodynamics (PD) and eventually treatment outcome. In the field of cancer management, several clinical studies have addressed the effect of timing medications for treatment optimization – chronotherapy – with promising results [8] , [12] , [13] , [14] . Giacchetti and colleagues reported data from three international Phase III clinical trials involving 842 patients (345 females and 497 males) treated with 5-fluorouracil, leucovorin and oxaliplatin administered as chronomodulated or conventional infusions [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Another study on 186 metastatic colorectal cancer patients in a randomized multicenter phase III trial also reported that oxaliplatin, 5-FU, and chronoFLO delivered by chrono-modulated infusion reduced ~ fivefold the rate of severe mucosal toxicity and ~ 50% functional impairment from peripheral sensitive neuropathy compared with constant drug delivery (14% vs. 76% and 16% vs. 31%, respectively) [ 329 ]. Furthermore, timed administration of irinotecan was performed in 31 cancer patients and demonstrated that chrono-mediated infusion of irinotecan from 2:00 a.m. to 8:00 a.m. induced less severe diarrhea and interpatient variability compared with the conventional 30-min infusion in the morning [ 351 ]. A very recent clinical study evaluated the effect of immunotherapy time-of-day infusion on the overall survival of patients with advanced melanoma.…”
Section: Potential Application Of Clock-associated Therapy In Cancer ...mentioning
confidence: 99%
“…at 1800 before or after doxorubicin) caused fewer complications and renal toxicity than administration of doxorubicin in the evening and cisplatin in the morning (Hrushesky, 1985;Sothern et al, 1989;Levi et al, 1990). Likewise, chronotherapy trials of patients with metastatic colorectal cancer showed that timed combination therapy with irinotecan, oxaliplatin, 5-fluorouracil (5-FU), and leucovorin resulted in delayed time to progression and increased overall survival with increased tolerance and safety, compared to routine chemotherapy (Levi et al, 1997;Gholam et al, 2006;Innominato et al, 2020b).…”
Section: Chrono-chemotherapymentioning
confidence: 99%